2023
DOI: 10.1002/smll.202207360
|View full text |Cite
|
Sign up to set email alerts
|

Amoeba‐Inspired Magnetic Venom Microrobots

Abstract: Nature provides a successful evolutionary direction for single‐celled organisms to solve complex problems and complete survival tasks – pseudopodium. Amoeba, a unicellular protozoan, can produce temporary pseudopods in any direction by controlling the directional flow of protoplasm to perform important life activities such as environmental sensing, motility, predation, and excretion. However, creating robotic systems with pseudopodia to emulate environmental adaptability and tasking capabilities of natural amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…[ 25–31 ] It is also worth noting that in addition to light‐propelled micro/nanorobots, magnetic micro/nanorobots have also played an invaluable role in soft robotics, with an emphasis on environmental and biomedical applications. [ 32–34 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 25–31 ] It is also worth noting that in addition to light‐propelled micro/nanorobots, magnetic micro/nanorobots have also played an invaluable role in soft robotics, with an emphasis on environmental and biomedical applications. [ 32–34 ]…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29][30][31] It is also worth noting that in addition to light-propelled micro/nanorobots, magnetic micro/nanorobots have also played an invaluable role in soft robotics, with an emphasis on environmental and biomedical applications. [32][33][34] Our group has developed a Pt-Pd/hematite Janus structure to fragment polymers; for example, high-molecular mass PEG was photofragmented under UV irradiation. [35] We demonstrated that we can digest and decompose various solid polymers using BiVO 4 and Bi 2 WO 6 microrobots.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, droplet robots have received much attention due to their excellent performance, and a large number of droplet robots have been proposed that can realize reconfigurable and adaptive driving in different environments, including ferrofluid droplet robots, water droplet robots, , organic droplet robots, and liquid metal droplet robots. The droplet robots are human and environmentally friendly, as the flexibility of droplet robots can cause less damage to the surroundings or the objects in contact with the robot. Due to their liquid nature, droplet robots can be reconfigured and realize large-scale deformation without limitation.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with those actuated by other actuation methods including electric field, light, , and thermal field, magnetically actuated droplet robots can be controlled by using noninvasive magnetic fields to accomplish complex operations and on-demand tasks without generating heat and pollution and the robot is not affected by the object light transmittance as well. Thus, human and environmentally friendly droplet robots play a significant role in microfluidics, object manipulation, ,, chemical reactions, ,, targeted drug delivery, , and pressure sensor . However, existing droplet robots always struggle to maintain fixed and complex shapes due to their fluidity, which makes them difficult to manipulate objects with large inertia.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a novel amoeba‐inspired magnetic droplet robot has been developed, which can perform applications such as in situ chemical reactions, thrombolysis, and phagocytosis. [ 14 ] These magnetic elastomers and fluid‐like magnetic robots (hereafter referred to as droplet robots) exhibit high deformability, enabling them to modify their shape to match the geometry of the surrounding environment, thereby facilitating their movement through tight channels. They also possess the capability to divide into smaller robots (fission) or amalgamate into larger robots (fusion).…”
Section: Introductionmentioning
confidence: 99%